Barriers to Growth-Enhancing Structural Transformation: The Role of Subnational Differences in Intersectoral Productivity Gaps - Saumik Paul; Dhushyanth Raju (Institute of Labor Economics (IZA), 2021)
The movement of workers from the farm sector to a more productive nonfarm sector has failed to generate significant gains in labor productivity in recent decades in many developing countries. This paper offers a new perspective into the barriers to growth-enhancing structural transformation, combining structural modeling with enterprise census data from Ghana. We argue that subnational differences in the intersectoral productivity gap between the nonfarm informal and formal sectors constrain the productivity gain from structural transformation. In Ghana, intersectoral productivity gaps among the richer regions are on average three times larger than among the poorer regions. We model the disparity in regional intersectoral productivity gaps as reflecting the disparity in the regional misallocation of labor between the informal and formal sectors and identify misallocation as the output wedge between the informal and formal sectors. Simulations suggest that a more productive nonfarm informal sector reduces the disparity in regional intersectoral productivity gaps and, in turn, increases national productivity and the contribution of structural transformation to national productivity. For example, a 90-percent reduction in the disparity in regional intersectoral productivity gaps raises Ghana's national aggregate productivity by 11.9 percent and the contribution of structural transformation to productivity by 19.7 percent.
Keywords: D24; F15; F43; N10; O11; O14; O47; 330; structural transformation; misallocation of resources; labor productivity; nonfarm enterprises; subnational regions; informal and formal sectors; Ghana